2013
DOI: 10.1111/jgs.12204
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Strength, Quadriceps Power, and Gait Speed in Older U.S. Adults with Diabetes Mellitus: Results from the National Health and Nutrition Examination Survey, 1999–2002

Abstract: Objectives To examine the independent association of diabetes (and its duration and severity) with quadriceps strength, quadriceps power, and gait speed in a national population of older adults. Design Cross-sectional nationally representative survey. Setting U.S. Participants We examined 2573 adults ≥50 years of age in the National Health and Nutrition Examination Survey 1999–2002 who had assessment of quadriceps strength. Methods Diabetes was ascertained by questionnaire. Measurement of isokinetic kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
102
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 28 publications
(71 reference statements)
9
102
1
2
Order By: Relevance
“…Un estudio demostró que la diabetes estaba asociada a una menor densidad y calidad muscular y menor fuerza en la rodilla y el tobillo (28) y también a una menor distancia de recorrido en 6 min (29) . Asimismo, se considera que la presencia del estado proinflamatorio como consecuencia de la resistencia a la insulina, producirá una reducción en la fuerza y poder muscular, lo cual, aunado a la neuropatía periférica, explicarían aún más la presencia de una velocidad de la marcha lenta en adultos mayores diabéticos (30) . La población estudiada fue extraída de la comunidad, y con una deambulación sin asistencia, por lo que no se incluyó adultos mayores con diabetes que haya producido daño secuelar a nivel de miembros inferiores o sobre la capacidad cardiaca, respiratoria o neurológica que altere la marcha.…”
Section: Discussionunclassified
“…Un estudio demostró que la diabetes estaba asociada a una menor densidad y calidad muscular y menor fuerza en la rodilla y el tobillo (28) y también a una menor distancia de recorrido en 6 min (29) . Asimismo, se considera que la presencia del estado proinflamatorio como consecuencia de la resistencia a la insulina, producirá una reducción en la fuerza y poder muscular, lo cual, aunado a la neuropatía periférica, explicarían aún más la presencia de una velocidad de la marcha lenta en adultos mayores diabéticos (30) . La población estudiada fue extraída de la comunidad, y con una deambulación sin asistencia, por lo que no se incluyó adultos mayores con diabetes que haya producido daño secuelar a nivel de miembros inferiores o sobre la capacidad cardiaca, respiratoria o neurológica que altere la marcha.…”
Section: Discussionunclassified
“…In this regard, previous studies linking diabetes with reduced walking speed (39,(43)(44)(45) have attributed this association to the accelerated loss of skeletal muscle strength that is commonly seen in older adults with this metabolic disease (23,24). To address whether diabetes-related muscle impairments could mediate the association between diabetes and low walking speed, researchers from the InCHIANTI study assessed walking performance and lower-extremity muscle mass, strength and power in a sample of 835 older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…A lower amount of physical activity is a risk factor for type-2 diabetes mellitus [36], and gait speed is associated with the prevalence of diabetes mellitus [22,37]. TFS is positively related to physical activity [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…One cross-sectional study also showed that poor muscular strength and power of lower-limb muscle groups are associated with the prevalence of diabetes mellitus [22]. One longitudinal study suggested that poor muscular strength (as quantified by a combination of leg and bench presses) is a risk factor for the metabolic syndrome [23].…”
Section: Discussionmentioning
confidence: 99%